Isolation and Characterization of Dextransucrase from Bacterial Isolate Sugar Cane - A.E. Zainal Hasan; Laksmi Ambarsari; . Hasim; Aisyah Girindra (Department of Chemistry, 2001)
Dextransucrase is a glucasyltransferase that catalyzes the transfer of an alpha-D-glucopyranosyl group from sucrose to dextran and releasing the fructose. Enzyme activity was determined by measuring the initial reaction rate of fructose released from sucrose. A standard unit (U) is defined as the amount of enzyme that catalyzes the formation of 1 umol of D-fructose per mg of protein per minute. Dextransucrase was produced by fed-bath cultures of isolate bacterial from sugar cane in a mixture containing sucrose (10 % b/v) in themedium fermentation. Extracellular dextransucrase was obtained from bacterial isolate from sugar cane. Final culturedextransucrase activity was 0,2776 Ulmg of protein. Dextransucrase purified by ethanol 80 % showed activity of 4,2077 Ulmg of protein or activity increase 1515,75 %. Temperature optimum was 40 OC and pH optimum was 7.6. All of the metal increased the activity, except HgC12. Dectransucrase kinetics constants, Km is 3,00 mM and Vmaks is 3,5559 unit/mg of proteinlmin. Molecular weight is 95.155 kDa.